Hadith #2766 - Sunan Abi Dawud - Abdur Rahman bin 'Amr al-Awza'i عبد الرحمن بن عمرو أبو عمرو الأوزاعي; Abu Ja'far al-Nafaili عبد الله بن محمد أبو جعفر النفيلي الحران; Hsan bin Atyh al-Mharby حسان بن عطية المحاربي مولاهم; Isa bin Yonus bin Abi Ishaq عيسى بن يونس بن أبي إسحاق; Jubayr bin Nufayr al-Hadrami (Sunan Abi Dawud)
Al Miswar bin Makhramah and Marwan bin Al Hakam said “They agreed to abandon war for ten years during which the people which have security on the basis that there should be sincerity between them and that there should be not theft or treachery.
Grade: Hasan

Hadith #2882 - Sunan Abi Dawud - Abdur Rahman bin 'Amr al-Awza'i عبد الرحمن بن عمرو أبو عمرو الأوزاعي; Amr bin Shu'aib bin Muhammad عمرو بن شعيب بن محمد السهمي; Hsan bin Atyh al-Mharby حسان بن عطية المحاربي مولاهم; Shu'aib bin Muhammad bin 'Abdullah شعيب بن محمد بن عبد الله بن عمرو (Sunan Abi Dawud)
A man said: Messenger of Allah, my mother has died ; will it benefit her if I give sadaqah on her behalf ? He said: Yes. He said: I have a garden, and I call you to witness that I have given it as sadaqah on her behalf.
Grade: Sahih

Hadith #4030 - Sunan Abi Dawud - Abdur Rahman bin Thabit عبد الرحمن بن ثابت بن ثوبان العنسي; Abu al-Mnyb al-Jrshy أبو المنيب الجرشي; Hashim bin al-Qasim bin Muslim هاشم بن القاسم أبو النضر - قيصر; Hsan bin Atyh al-Mharby حسان بن عطية المحاربي مولاهم; ibn Umar; Uthman bin Muhammad (Sunan Abi Dawud)
Garment of disgrace.
Grade: Hasan

Hadith #4061 - Sunan Abi Dawud - Abdur Rahman bin 'Amr al-Awza'i عبد الرحمن بن عمرو أبو عمرو الأوزاعي; Abu Ja'far al-Nafaili عبد الله بن محمد أبو جعفر النفيلي الحران; Hsan bin Atyh al-Mharby حسان بن عطية المحاربي مولاهم; Jabir ibn 'Abdullah; Mskyn bin Bkyr al-Hrany مسكين بن بكير الحراني أبو عبد الرحمن; Muhammad bin al-Munkdar bin 'Abdullah محمد بن المنكدر بن عبد الله بن الهدير; Uthman bin Muhammad; Waki' bin al-Jarrah وكيع بن الجراح (Sunan Abi Dawud)
The Prophet (ﷺ) said: Wear your white garments, for they are among your best garments, and shroud your dead in them. Among the best types of collyrium you use is antimony (ithmid) for it clears the vision and makes the hair sprout.
Grade: Sahih

Hadith #4291 - Sunan Abi Dawud - Abdur Rahman bin 'Amr al-Awza'i عبد الرحمن بن عمرو أبو عمرو الأوزاعي; Abu Ja'far al-Nafaili عبد الله بن محمد أبو جعفر النفيلي الحران; Hsan bin Atyh al-Mharby حسان بن عطية المحاربي مولاهم; Isa bin Yonus bin Abi Ishaq عيسى بن يونس بن أبي إسحاق; Jubayr bin Nufayr al-Hadrami (Sunan Abi Dawud)
The Prophet (ﷺ) said: A man called al-Harith ibn Harrath will come forth from Ma Wara an-Nahr. His army will be led by a man called Mansur who will establish or consolidate things for Muhammad’s family as Quraysh consolidated them for the Messenger of Allah (ﷺ). Every believer must help him, or he said: respond to his sermons.
Grade:

Hadith #4291 - Sunan Abi Dawud - Abdur Rahman bin 'Amr al-Awza'i عبد الرحمن بن عمرو أبو عمرو الأوزاعي; al-Walid bin Muslim al-Quraishi الوليد بن مسلم القرشي; Hsan bin Atyh al-Mharby حسان بن عطية المحاربي مولاهم; Mu'ml bin al-Fadl مؤمل بن الفضل (Sunan Abi Dawud)
The Prophet (ﷺ) said: Allah will raise for this community at the end of every hundred years the one who will renovate its religion for it. Abu Dawud said: ‘Abd al-Rahman bin Shuriah al-Iskandarani has also transmitted this tradition, but he did not exceed Shrahil.
Grade: Sahih